Dietary quercetin attenuates oxidant-induced endothelial dysfunction and atherosclerosis in apolipoprotein e knockout mice fed a high-fat diet: A critical role for heme oxygenase-1 - Shen, Y.; Ward, Natalie; Hodgson, J.; Puddey, I.; Wang, Y.; Zhang, D.; Maghzal, G.; Stocker, R.; Croft, K. (2013)
Several lines of evidence indicate that quercetin, a polyphenol derived in the diet from fruit and vegetables, contributes to cardiovascular health. We aimed to investigate the effects of dietary quercetin on endothelial function and atherosclerosis in mice fed a high-fat diet. Wild-type C57BL/6 (WT) and apolipoprotein E gene knockout (ApoE−/−) mice were fed: (i) a high-fat diet (HFD) or (ii) a HFD supplemented with 0.05% w/w quercetin (HFD+Q), for 14 weeks. Compared with animals fed HFD, HFD+Q attenuated atherosclerosis in ApoE−/− mice. Treatment with the HFD+Q significantly improved endothelium-dependent relaxation of aortic rings isolated from WT but not ApoE−/− mice and attenuated hypochlorous acid-induced endothelial dysfunction in aortic rings of both WT and ApoE−/− mice. Mechanistic studies revealed that HFD+Q significantly improved plasma F2-isoprostanes, 24 h urinary nitrite, and endothelial nitric oxide synthase activity, and increased heme oxygenase-1 (HO-1) protein expression in the aortas of both WT and ApoE−/− mice (P<0.05). HFD+Q also resulted in small changes in plasma cholesterol (P<0.05 in WT) and plasma triacylglycerols (P<0.05 in ApoE −/−mice). In a separate experiment, quercetin did not protect against hypochlorite-induced endothelial dysfunction in arteries obtained from heterozygous HO-1 gene knockout mice with low expression of HO-1 protein. Quercetin protects mice fed a HFD against oxidant-induced endothelial dysfunction and ApoE−/− mice against atherosclerosis. These effects are associated with improvements in nitric oxide bioavailability and are critically related to arterial induction of HO-1.